Tear stability, corneal staining and dry eye symptoms in contact lens wearers - Norhani Mohidin,; Nur Natasha Zulkipli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study was to examine tear stability of contact lens wearers (CLW) in young Malay adults aged 18 and above and to compare the results with non-contact lens wearers (NCLW). Corneal staining and McMonnies Dry Eye Questionnaires (MDEQ) scores between habitual soft CLW and NCLW were also compared. It also aimed to find correlation between tear stability and MDEQ scores. Quasi-experimental and case control study was conducted among 53 participants (53 right eyes) at UiTM Vision Care, UiTM Puncak Alam Campus. Twenty six participants were habitual soft CLW and twenty seven were NCLW. Tear stability was measured using non-invasive tear break-up time (NIBUT) and invasive tear break-up time (TBUT). Corneal staining was measured using Efron Grading Scale and dry eye symptoms evaluated using MDEQ. Mean scores of NIBUT and TBUT for CLW were 5.23 ± 7.3 sec and 2.19 ± 2.41 sec respectively; for NCLW were 8.71 ± 4.33 sec and 3.00 ± 1.69 sec respectively. There were significant differences in NIBUT (Mann-Whitney U, p = 0.0001) and TBUT (Mann-Whitney U, p = 0.001) between the CLW and NCLW. There was also significant difference in percentage of corneal staining found between the CLW (22.6%) and NCLW (7.5%), (Chi-square, p = 0.013). However no significant difference was found in MDEQ scores between the CLW (7.54 ± 3.62) and the NCLW (8.15 ± 3.38) group, (Mann-Whitney U, p = 0.42). There were also no correlations found between tear stability and MDEQ scores in the two groups. The results of this study showed NIBUT and TBUT values were significantly higher in NCLW than in CLW and corneal staining was more extensive in CLW. Contact lens practitioners need to be aware of changes in tear stability as results of contact lens wear and take the necessary action to improve on the management of their patients during aftercare consultation.